2017
DOI: 10.3389/fnins.2017.00390
|View full text |Cite
|
Sign up to set email alerts
|

Weaker Functional Connectivity Strength in Patients with Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is related to cognitive impairments and increased risk for dementia. Neuroimaging studies have demonstrated T2DM-related brain structural and functional changes which are partly associated to the cognitive decline. However, few studies focused on the early neuroimaging findingsin T2DM patients. In this study, a data-driven whole-brain resting state functional connectivity strength (rsFCS) methodwas used to evaluate resting functional changes in 53 T2DM patients compared with 55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 95 publications
1
15
0
Order By: Relevance
“…Through correlation analysis, we found that the abnormal functional connectivity of the T2D group was positively correlated with clinical variables of diabetes, such as FPG, 2hPG, HbA 1c , and HOMA-IR. A correlation between HbA1c levels and brain function connectivity has also been reported in previous studies (Xia et al, 2015; Liu et al, 2017). Studies have shown that poor glycemic control leading to long-term chronic exposure to hyperglycemia may be a decisive factor in T2D brain damage (Manschot et al, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Through correlation analysis, we found that the abnormal functional connectivity of the T2D group was positively correlated with clinical variables of diabetes, such as FPG, 2hPG, HbA 1c , and HOMA-IR. A correlation between HbA1c levels and brain function connectivity has also been reported in previous studies (Xia et al, 2015; Liu et al, 2017). Studies have shown that poor glycemic control leading to long-term chronic exposure to hyperglycemia may be a decisive factor in T2D brain damage (Manschot et al, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…The disruption in the balance between long- and short-range FCD may suggest a shift from the costly metabolic connection to an economic connection. Previous studies have reported alterations in long- and short-range functional connectivity strength ( Liu et al, 2017 ), and local and remote brain activity synchronization in T2DM patients ( Liu et al, 2016 ). The present study further suggests that T2DM patients have more short-range connections and fewer long-range connections.…”
Section: Discussionmentioning
confidence: 99%
“…As an approach for functional integration, the analysis of long- and short-range functional connections facilitates the investigation of brain dysfunction in patients with schizophrenia ( Guo et al, 2015 ), minimal hepatic encephalopathy ( Qi et al, 2015 ), non-alcoholic cirrhosis after liver transplantation ( Zhang et al, 2015a ), end-stage renal disease ( Zhang et al, 2015b ) and conduct disorder ( Lu et al, 2017 ). Previous studies have also suggested that T2DM patients may suffer from cognition decline linked to alterations in long- and short-range brain functional synchronization and functional connectivity strength ( Liu et al, 2016 , 2017 ). In addition to the aforementioned neuroimaging indicators, the functional connectivity density (FCD), which quantifies the number of functional connections between a given voxel and the remaining voxels in the entire brain, is a graph theoretical indicator to analyze the complex brain networks ( Tomasi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DC in RESTplus software was used to calculate the DC value based on correlation thresholds (absolute value of Pearson's r > 0.2) to exclude weak correlations, which may be caused by signal noise based on previous studies ( 22 , 33 , 34 ). Then smooth was performed with a 6 × 6 × 6 mm 3 Gaussian kernel.…”
Section: Methodsmentioning
confidence: 99%
“…Kolmogorov–Smirnov test ( 33 ) was applied to detect the normality of the continuous variables, including the demographic data and biochemical characteristics of the T2DM subjects and HCs. Independent two-sample t -tests were used if the data meet normal distribution and variance homogeneity; otherwise, Mann–Whitney non-parametric tests were used.…”
Section: Methodsmentioning
confidence: 99%